DSM Borderline Criterion Function Across Age-Groups: A Cross-Sectional Mixed-Method Study. (September 2019) - Sharp, Carla; Steinberg, Lynne; Michonski, Jared; Kalpakci, Allison; Fowler, Chris; Frueh, B. Christopher; Fonagy, Peter
DSM-5 ( Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition ) Section II criteria for borderline personality disorder (BPD) lack developmental operationalization. The aim of the current study was to evaluate whether DSM criteria operate similarly across adolescents and adults to determine if developmental adjustment for DSM criteria was needed. Three age cohorts were recruited: adolescents (ages 12-17 years; n = 484), young adults (ages 18-25 years; n = 442), and adults (ages ≥26 years; n = 953). The Child Interview for DSM-IV BPD and the Structured Clinical Interview for DSM-IV Axis II disorders were administered to adolescents and adults, respectively. Item response theory methods were used to evaluate differential item (or criterion) functioning (DIF) of BPD criteria across adolescents and adults. Qualitative analyses were then used to evaluate the potential sources of DIF. Item response theory results demonstrated DIF across adolescents and adults for all DSM BPD criteria. Qualitative analyses suggested that the source of DIF was most likely due to rater/interviewer bias. Results furthermore suggested that behavioral criteria may represent the heterotypic features of BPD, while intra- and interpersonal criteria represent the homotypic features of the disorder. The article concludes with recommendations for developmentally informed guidelines for the assessment of BPD.